The Effect of the Lower Leg Sensory Feedback on Force Sense of the Knee Extensor Muscles in Healthy Young Men: A Cross-Sectional Study - Minoo Khalkhali-Zavieh; Bahram Amirshakeri; Abbas Soltani-Someh; Mina Ahmadi-Kahjoogh (Vesnu Publications, 2020)
Introduction: Sensory information is essential for controlling and modulating muscle force. The aim of this study is to examine the effect of the lower leg sensory feedback on the force sense of the knee extensor muscle.Materials and Methods: 22 healthy young men participated in this cross-sectional study through simple random sampling. Before and immediately following manipulation of skin sensory information, the mean error of three times of reproducition of the target force [50% of Maximum voluntary isometric contraction (MVIC)] of the knee extensor muscles was measured using a special dynamometer and reported. The force sense of the knee extensor muscles was examined at an angle of 60 degrees of flexion. The test was conducted in three conditions: normal (control) state, after using a thick sponge on the distal end of the dominant leg, and after placing a bag of small ice blocks on the distal end of the dominant leg for 20 minutes. To evaluate the force sense, the force reproduction methods were used in ipsilateral and contralateral knee. Repeated measures analysis of variance (ANOVA) and paired t-test were used to compare different conditions.Results: By manipulating the leg sensory information, no significant change was observed in the force reproduction error (absolute, constant, and variable errors) of the ipsilateral leg (P > 0.05). However, a significant change was observed in the force reproduction error in contralateral side (P < 0.05).Conclusion: It seems that the leg sensory information plays an important role in accurate perception of the force at contralateral knee joint. Therefore, signals delivered by the sensory afferents are important in understanding and controlling force.